Workshop dan Pendampingan Pembuatan Media E-Learning Guna Mendukung Pembelajaran Blended Learning Untuk Guru-Guru MGMP Biologi SMA se-KabupatenTanjung Jabung Barat - Johan Wicaksana, Evan; Johari, Asni; Naswir, Muhammad; Natalia, Desfaur; Muswita (Jurnal SOLMA, 2024)
Background: Blended learning is a learning approach that combines face-to-face (synchronous) and non-face-to-face (asynchronous) learning. This learning approach has been implemented in various schools in Tanjung Jabung Barat Regency. However, in its implementation there are obstacles, one of which is the teacher's lack of knowledge in developing appropriate media that can be used in implementing blended learning. The aim of this service activity is to train the creation of e-learning media to support blended learning for MGMP Biology teachers throughout Tanjung Jabung Barat Regency. Method: The workshop and mentoring activities are carried out by delivering material, discussion and practice. Result: all activities run well. Every teacher can create e-learning media for their learning. Conclusion: as many as 100% of participants stated that PPM activities were very useful, and 93% of participants were committed to implementing the e-learning media developed in their learning process.